Pembuatan Masker Gel dari Ekstrak Wortel (Daucus Carota L) - Oktavia Agustina Maretti; Mitra Lusiana (Tamasya : Jurnal Pariwisata Indonesia, 2025)
In helping to support the appearance and confidence of the skin needs to be treated especially for dry skin. Having a dry facial skin causes discomfort because the cosmetics used will be difficult to stick to the skin. In addition, weather factors, the use of unsuitable cosmetics, exposed to excessive sun exposure, and unhealthy lifestyles can cause the skin to become dry. The purpose of this study was to determine the process of making gel masks from carrot extracts and seen from laboratory tests, organoleptic tests and hedonic tests. This study uses quantitative methods with an experimental approach. Data collection techniques through observation, documentation and observation sheets that can be seen from the results of laboratory tests, organoleptic tests (texture, color, aroma, adhesion) and hedonic tests (panelists). The results of the study obtained from the results of laboratory tests by looking at the pH level of each formulation are in a safe range of 4-5. In the organoleptic test, panelists declared F1 as a preparation of less thick, orange, and lack of scented in carrot. In the F2 formulation, panelists declare as a texture preparation that is thick, orange, and scented typical of carrots. In the F3 formulation, the panelists declare that the preparation is less thick, less orange, and a typical carrot scented. In the F4 formulation, panelists declare as a very thick, non -orange preparation. And very scented typical of carrots. In the adhesion of the panelist states from all formulations that F4 is very attached. In the hedonic test, the preparation that many panelists like, namely the F4 preparation, is very thick, not orange and very scented typical of carrots. Thus the gel mask of carrot extract can be used as material for making gel masks seen from laboratory tests, organoleptic tests, and hedonic tests.